Real-time Tracking System for smart factories - Omar Dere; Ibrahem Arda (My University, 2023)
Industry real-time tracking applications can be used to collect and analyze data about manufacturing processes. Industrial engineers can convert it into information for increased productivity. More data means better decisions and fine-tuned production processes that make maximum use of resources. Continuous monitoring also ensures a better quality of production. The smart factory is at the heart of industry and describes a production environment that is self-organizing with the help of sensors and intelligently connected devices. For this project we are going to design hardware-system to track what is happening within production process, provide the necessary information at the right time and in the proper format and control element when unplanned changes and details appear. And that functionalities are needed for essential part of intelligent manufacturing. In this project, we will use one microcontrollers (Arduino), sensors, camera, motors and developing small software to monitor the output of hardware system.